Stuck! Welfare state dependency as lived experience. Issue 3 (26th May 2020) - Andersen, Ditte
ABSTRACT: The concern that public support may spur dependency has been voiced throughout the history of welfare states. Nevertheless, little research examines the experience of welfare state dependency in the context of recipients' everyday lives. This paper provides an in-depth analysis of a case involving Anna, who depends on the Danish welfare system for financial benefits and other forms of support. The study spans five years from age 19 to 24, and includes some of the significant others in Anna's everyday life – her mother, who also depends on welfare, and her caseworkers. By situating Anna's experiences in a temporal and social context, the case study advances a nuanced understanding of welfare state dependency and identifies three driving forces of the experience: (1) the concern about intergenerational transmission of dependency that spurs a shared sense of hopelessness among Anna and her significant others; (2) the recurrent changes of diagnoses that adds to the feeling of dependency by repeatedly generating waiting time, e.g. for new psychiatric assessments; (3) the system's requirement to produce numerous but sketchy future plans that lack real-world plausibility. The case study clarifies the importance that respectable exits out of welfare state dependency are not only imaginable but also believable.